The Influence of Compensation and Work Motivation on Employee Loyalty Through Job Satisfaction as an Intervening Variable: (Study at PT Tokoh Indonesia Muda Executive) - Firli Adri Ridhotama; Sri Wahyu Lelly Hana Setyanti; Diana Sulianti K. Tobing (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The aim of this research is to determine the effect of compensation and work motivation on employee loyalty through satisfaction as an intervening variable. This research will test the influence directly and indirectly. This research uses descriptive research methods with quantitative research. The number of samples used in this research was 60 respondents. By using a saturated sampling technique where the entire population is sampled. Using SmartPLS version 3, the analysis results show that 1) compensation has a significant effect on job satisfaction 2) work motivation has a significant effect on job satisfaction 3) compensation has a significant effect on loyalty 4) work motivation has no significant effect on loyalty 5) job satisfaction has no significant effect on loyalty, 6) job satisfaction does not mediate the effect of compensation on loyalty. 7) job satisfaction does not mediate the effect of work motivation on loyalty.